Complicit: The Creation Of and Collaboration With Intelligent Machines. (1st March 2019) - Rehm, M Casey
Abstract : How do the biases, constraints and opportunities inherent within contemporary models of intelligence lead to new aesthetics? Artificial intelligence has been central to the work of designer and algorithmic consultantM Casey Rehm for over a decade. Here he presents recent results of his efforts, produced within his Los Angeles multidisciplinary practice Kinch – from speculative cityscapes to a single‐family house.